The Designing a Knitted Bag To Carry Baby Equipment Aged 0-1 Years - Salsabila Hermalia Putri; Edi Putra (Penerbit Itenas, 2023)
A bag is a package or container in the form of a square or something, usually strapped, used to store, store or carry something. A bag is also an item that must be used by all groups, both men and women as a complement to fashion, therefore increasing income, even lifestyle and population level so that there are also more marriage rates and young families with children. Supporting equipment for the convenience of babies interacting in their daily lives must also be paid close attention to by parents, including introducing their environment either through a trip, traveling or visiting family, friends and other people around. So that on this trip it is necessary to bring baby equipment and require storage that can accommodate the equipment and needs needed by the baby. In this study the Design Thinking methodology was used. The benefit of this research is to produce a product bag for carrying baby equipment that has lots of space for small compartments and the convenience of carrying, storing and retrieving baby equipment products in the bag.